Twentieth-century modern-colonial irrigation development in Banten: Technological review of Pamarayan old stuwdam - Syahid, Mushab Abdu Asy; Wigati, Restu (Jurnal Fondasi, 2023)
The Bendung Lama Pamarayan in Panyabrangan, Serang, is an old movable weir vital in regional irrigation and cultivation in Banten's history. However, current historical and archaeological studies provide limited technical analysis of how its system and management worked in the past. To address the issue, this study focuses on the technological significance of the Pamarayan weir or stuwdam as an integral part of the water resources improvement program in the early twentieth-century Banten. Archival records and a heuristic approach of Digging 4 Data are employed to understand the dynamics of the Pamarayan water catchment project at Ciujung riverine constructions throughout history. The study identifies several factors that led to the failure of its sustainability, including changes in the natural hydrological regime of the Ciujung River and ineffective maintenance practices. The research findings also retrospectively highlight the early development of modern hydraulic engineering in Indonesia, and suggest potential extensions for heritage conservation and community empowerment of the historical civil engineering structure.